Perkembangan Bentuk Produk, Motif dan Fungsi Produk Songket Melayu Pekanbaru Riau - Mulyeti Marzal, Drs. Erwin A, M.Sn., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2016)
The purpose of this study is to describe the development of shape, motif, and function of songket’s product in Melayu Pekanbaru Riau. The method of this reseach is qualitative with descriptive approach. The result shows that the product of traditional Malay’s songket expand from clothes only to other house wear. The forms of the product are derived from the pattern of flora (55 motifs), fauna (14 motifs), and nature (11 motifs). The physical function of songket’s product in Melayu Pekanbaru Riau develops in terms of function from life function which develop to various types of Malay songket’s product.Keywords: Product’s shape, Motif, Function, Songket’s product in Melayu Pekanbaru Riau